The Clinical Outcome of COVID-19 Infection on Chronic Diabetic Complications Patients - Wardani, Erlisa Pramodya; Tri Pudy Asmarawati; Isnin Anang Marhana; Hermina Novida (Current Internal Medicine Research and Practice Surabaya Journal, 2024)
Introduction: COVID-19 is an infectious disease resulting from the SARS-CoV-2 virus. The virus targets the respiratory system and leads to a significant number of fatalities worldwide. Consequently, it was officially classified as a pandemic in 2020. The Covid varians is now being monitored by the World Health Organization. Diabetes mellitus is one of the disorders that might deteriorate following an infection. Diabetes mellitus and its associated comorbidities continue to pose a significant health challenge in Indonesia, while it is also a focus of concern of the Sustainable Development Goals (SDGs). The study was aimed to assess the risks and outcomes associated with COVID-19 infection and the long-term consequences of diabetes mellitus.Methods: This was a descriptive study using a retrospective design. Research data were taken from the medical records of patients confirmed positive for COVID-19 infection and also had chronic complications of diabetes mellitus who were treated at Dr Soetomo General Academic Hospital, Surabaya, Indonesia in 2021. There were 156 patients who met the criteria of this research.Results: There were 156 patients (97 males, 59 females). The average age of the patients was 58, while most of the patients (84%) died and the rest of the patients (16%) survived. Most of the patients with fatality (55.8%) were those with critical severity level and complications of microangiopathy, while the patients who survived (10.3%) were those with moderate severity level and complications of microangiopathy. Conclusion: COVID-19 patients with diabetes and comorbidities had a higher mortality rate than those who recovered, while most of the patients with fatality were those with significant COVID-19 and diabetic microangiopathy complications.